FGF2/FGFR signaling promotes cumulus–oocyte complex maturation in vitro. Issue 2 (February 2021) - Du, Chao; Davis, John S; Chen, Chao; Li, Zan; Cao, Ye; Sun, Hui; Shao, Bao-Shun; Lin, Yu-Xin; Wang, Yong-Sheng; Yang, Li-Guo; Hua, Guo-Hua
Abstract : Fibroblast growth factor 2 (FGF2), a member of FGF family, binds with FGF receptors (FGFR) to initiate biological functions in various somatic cells. However, little is known regarding the role of FGF2/FGFR on oocyte meiosis. In this study, we investigated expression patterns and functions of FGF2/FGFR during in vitro maturation (IVM) of mouse cumulus-oocyte complexes (COCs). Among four FGFRs, Ffgr1 was the most abundant in COCs. The transcripts for Fgf2 and Ffgr1 in COCs increased during IVM. Ffgr1 was present in oocytes and cumulus cells, while Fgf2 was present in only cumulus cells. Treatment of COCs with the selective FGFR inhibitor SU5402 blocked oocyte meiotic progression and downregulated expression of Bmp15 and Gdf9 . In contrast, supplement of FGF2 promoted oocyte meiotic progression and upregulated Bmp15 and Gdf9 expression. Inhibition of FGFR with SU5402 reduced cumulus expansion and expressions of Ptx3, Has2 and Tnfaip6 . Treatment with FGF2 increased Ptx3 and Has2 expression. Inhibition of FGFR had no effect on meiotic progression of denuded oocytes (DOs). However, co-culture of DOs with COCs or supplementation with FGF2 promoted meiotic progression of DOs. Inhibition of FGF2/FGFR signaling also downregulated Ffgr1 expression, while supplemental FGF2 upregulated Fgfr1 expression. Furthermore, inhibition of FGFR in COCs interrupted the c-Mos/MAPK pathway and maturation-promoting factor (MPF), as indicated by downregulation of oocyte c-mos and Ccnb1 transcripts, respectively. Overall, this study suggests that FGF2 produced by cumulus cells, activates a FGF2/FGFR autocrine/paracrine loop within COCs to regulate cumulus expansion and oocyte meiosis. These findings reveal a novel role for FGF2/FGFR signaling during in vitro maturation of COCs.